'They’d rather go play footy': an exploratory study of the enjoyment and benefits of the arts in Western Australia’s remote Murchison region - Anwar McHenry, Julia (Wiley-blackwell, 2011)
The role of the arts in the revitalisation and strengthening of Australia’s rural, remote, and Indigenous communities has been of particular interest to Australian State and Federal Governments, as reflected through various policy and positioning documents. In order to understand the relationship between the arts and communities, it is important to explore why people engage in the arts and what might be some of the barriers to that engagement. For the rural, remote and Indigenous communities of the Murchison Region, the arts has been a useful way of reaching and engaging with residents to build a stronger sense of community, provide light relief and entertainment, and facilitate communication among community members, government, and industry. However, there are several barriers that impact on the viability of arts projects. These barriers are amplified in rural and remote areas, and particularly for the three case study communities of the Murchison Region for a number of reasons. These include the transient nature of the population, a lack of resources, isolation and remoteness, and local politics, culture and history. The arts can provide a context in which other non-arts related outcomes, such as health, capacity building, income generation, and so on, are facilitated and achieved. It is important for policy makers to recognise and address the barriers which hinder activity and serve to lessen the impact of the arts on communities.